2022
DOI: 10.1002/ps.7108
|View full text |Cite
|
Sign up to set email alerts
|

Species boundary and phylogeographical pattern provide new insights into the management efforts of Megacopta cribraria (Hemiptera: Plataspidae), a bean bug invading North America

Abstract: BACKGROUND Correct identification together with information on distribution range, geographical origin and evolutionary history are the necessary basis for the management and control of invasive species. The bean bug Megacopta cribraria is a crucial agricultural pest of soybean. Recently, M. cribraria has invaded the United States and spread rapidly, causing severe reductions in soybean yields. However, the species boundary and phylogeographical pattern of this invasive bean bug are still unclear. RESULTS The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, due to rare recombination, maternal inheritance, and a relatively high evolutionary rate, mitochondrial genomes are perceived as effective markers for resolving phylogenetic relationships in insects. The genome of this organelle has been widely used for both deeply divergent lineages and recently radiated groups [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to rare recombination, maternal inheritance, and a relatively high evolutionary rate, mitochondrial genomes are perceived as effective markers for resolving phylogenetic relationships in insects. The genome of this organelle has been widely used for both deeply divergent lineages and recently radiated groups [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in cases involving the incomplete lineage sorting (ILS) of nuclear genes (Firneno et al, 2020). A large number of studies have shown that the use of mitogenome data can effectively identify specimens, discover cryptic species where few morphological differences can be observed (Liu et al, 2020; Zheng et al, 2020), and delimit species boundaries in species‐complexes with morphological variants that have puzzled taxonomists for many years (Amarasinghe et al, 2023; Zhu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, comparing mitochondrial gene structure and genetic composition between species can provide crucial insights into the evolution of related species [3,12,13]. Benefiting from advances in high-throughput sequencing technology, an increasing number of mitogenomes have been sequenced among the Hemiptera [14][15][16][17] and have been widely used for mitochondrial structure comparison, phylogenetic analysis at different taxonomic levels, species delimitation, population genetic structure, and biogeographic studies [7,[18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%